(untitled) (Journal of Plant Disease Sciences, 2025)
Four cultivars of foxtail millet were obtained from the Department of Seed Technology, Dr. PDKV, Akola, and the Krishi Vigyan Kendra (KVK), Buldhana, Maharashtra, for the present investigation. These cultivars were evaluated for the presence of seed-borne mycoflora using four standard seed health testing techniques as prescribed by the International Seed Testing Association (ISTA), namely the standard blotter paper method, agar plate method, rolled paper towel method, and deep freeze method. A total of seven seed-borne fungal species were identified during the study Aspergillus flavus Fusarium moniliforme Curvularia lunata Aspergillus niger Rhizoctonia solani Bipolaris sorokiniana Rhizopus stolonifer, and Among the methods employed, the standard blotter paper method proved to be the most effective for detecting seed-borne fungi in foxtail millet, recording the highest incidence (37.00%) of fungal contamination, this was followed closely by the agar plate method, which exhibited a fungal incidence of (35.06%).